Penerapan Metode Filter Gabor Untuk Analisis Fitur Tekstur Citra Pada Kain Songket - Leonardo Leonardo (Universitas Budi Darma, 2020)
Songket is a traditional Malay and Minangkabau woven fabric in Indonesia, Malaysia and Brunei. Songket is classified in the brocade woven family. Songket is hand woven with gold and silver threads generally worn at official occasions. The purpose of this study is to analyze the texture of songket fabric by using gabor filters. The results of the study stated that the texture output that appeared was strongly influenced by the magnitude of the frequency parameter values and the orientation of the image degrees. The greater the frequency value given, the results of the test use look brighter and blurry. Therefore the frequency value on the middle scale (f = 0.176) is considered the most appropriate for texture analysis. In addition to the frequency of orientation parameters are also able to show a tendency towards the texture in a certain direction. From the appearance of this fabric texture, the area suspected of having a good texture on the songket cloth.